Hubungan Iklan Grab di Televisi dan Intensitas Komunikasi Peer Group dengan Minat Menggunakan Grab - Try Anggara S, Bima; Pudjo Santosa, Hedi (Interaksi Online, 2019)
The purpose of this research is to study the relationship between exposure to Grab ads on Television and Peer Group Communication Intensity with Grab Interest. This research is a quantitative research with explanatory type. This study uses a non random technique with a sample size of 100 people, ages 17-35 years, domiciled in Semarang city, and has been exposed to Grab ads on Television. Based on the Hypothesis Test conducted using the Chi-Square test shows that there is a relationship between exposure to Grab ads on Television with an interest in using Grab, the findings related to the significance value is smaller than 0.05, 0.02. The relationship between these variables makes the theory of the Ad Exposure Process can be done. Means that the higher a person is exposed to advertising, it will encourage people's interest to take action. The next hypothesis test is performed using the Chi-Square test. The results of the Chi-Square Test show the relationship between communication with the Peer Group with an interest in using Grab, the findings related to the significance value of less than 0.01, namely 0,000. Obtained relationship between these required variables. Reference Groups can be accepted. The higher someone who supports with peers, the higher the interest of that person to use Grab. The Function of Group Reference Theory used in this study is a comparative function which means that someone will compare their behavior with supportive groups to find the best from these results.